PENGARUH KEPRIBADIAN, PROFESIONALISME DAN PENGALAMAN MENGAJAR TERHADAP KINERJA GURU MADRASAH TSANAWIYAH NEGERI 2 MANDAILING NATAL - Ibrahim .; Wahyu Surya Wibowo; Irwan Hengki Sukma; Yogie Pratama; Yudi Caesario (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The formulation in this research is how the personality influence, professionalism and experience teaching to the performance of teachers of the state of Tsanawiyah Madrasah 2 Mandailing Natal, and the purpose of this research is to know and analyze The influence of personality, professionalism and experience teaching to the performance of teachers of State Madrasah Tsanawiyah 2 Mandailing Natal. This research is a quantitative descriptive study. Data collection techniques are conducted through interviews, inquiry lists and documentation studies. The samples in this study were as many as 36 teachers. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The results of the test in unison showed that the personality, professionalism and experience demonstrated a very noticeable influence on the performance of teachers of state Madrasah Tsanawiyah 2 Mandailing Natal with a value Fcount 24,804 Ftable 2.87 and significance value of 0.000b. Adjusted number of R Square by 0. 671 or (67.1%) indicates that the percentage of contribution of independent variable influence (personality, professionalism and teaching experience) to the dependent variable (teacher performance) amounted to 67.1%. Partially, personality positively affects the performance of Guru Madrasah Tsanawiyah Negeri 2 Mandailing Natal with a value of tcount ttable (2,988 2,028) and significance value of 0. 005. Professionalism positively and significantly influence the teacher's performance of state Madrasah Tsanawiyah 2 Mandailing Natal with a value of tcount ttable (2,728 2,028) and a significance value of 0. 010. The teaching experience has positive and significant effect on the teacher's performance of Negeri Tsanawiyah 2 Mandailing Natal with a value of tcount ttable (4,580 2,028) and a significance value of 0. 000. The highest value of a regression coefficient is the teaching Experience (X3) of 0. 532 or 53.2% and is the most dominant variable affecting the teacher's performance of Negeri 2 Mandailing Natal.